Elite cross-country skiers do not reach their running VO2max during roller ski skating - Losnegard, T.; Hallén, J. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: Cross-country skiers' VO2max is often measured during treadmill running. However, VO2max during treadmill skiing with the diagonal stride technique is higher, whereas it is lower during double poling, another classical style technique. How these values compare to VO2max during ski skating in elite cross country skiers is not known. Therefore, this study compared VO2max during treadmill uphill running and treadmill roller ski skating.